Onset of Pup Locomotion Coincides with Loss of NR2C/D-Mediated Cortico-Striatal EPSCs and Dampening of Striatal Network Immature Activity - Dehorter, Nathalie; Michel, François J.; Marissal, Thomas; Rotrou, Yann; Matrot, Boris; Lopez, Catherine; Humphries, Mark D.; Hammond, Constance (Frontiers in Cellular Neuroscience, 2011)
Adult motor coordination requires strong coincident cortical excitatory input to hyperpolarized Medium Spiny Neurons (MSNs), the dominant neuronal population of the striatum. However, cortical and subcortical neurons generate during development large ongoing patterns required for activity-dependent construction of networks. This raises the question of whether immature MSNs have adult features from early stages or whether they generate immature patterns that are timely silenced to enable locomotion. Using a wide range of techniques including dynamic two photon imaging, whole-cell or single channel patch clamp recording in slices from Nkx2.1-GFP mice, we now report a silencing of MSNs that timely coincides with locomotion. At embryonic stage (as early as E16) and during early postnatal days, genetically identified MSNs have a depolarized resting membrane potential, a high input resistance and lack both inward rectifying (IKIR) and early slowly decaying (ID) potassium currents. They generate intrinsic voltage-gated clustered calcium activity without synaptic components. From postnatal days 5 to 7, the striatal network transiently generates synapse-driven giant depolarizing potentials (GDPs) when activation of cortical inputs evokes long lasting EPSCs in MSNs. Both are mediated by NR2C/D-receptors. These immature features are abruptly replaced by adult ones before P10: MSNs express IKIR and ID and generate short lasting, time-locked corticostriatal AMPA/NMDA EPSCs with no NR2C/D component. This shift parallels the onset of quadruped motion by the pup. Therefore, MSNs generate immature patterns that are timely shut off to enable the coordination of motor programs.